Pattern of Infectious Morbidity in HIV-Exposed Uninfected Infants and Children - Slogrove, Amy L.; Goetghebuer, Tessa; Cotton, Mark F.; Singer, Joel; Bettinger, Julie A. (Frontiers in Immunology, 2016)
Background: Almost 30% of children in Southern Africa are HIV exposed but uninfected (HEU) and experience exposures that could increase vulnerability to infectious diseases compared to HIV unexposed (HU) children. The mechanisms of HEU infant vulnerability remain ill-defined. This review seeks to appraise the existing clinical evidence of the pattern of HEU infant infectious morbidity to aid understanding of the potential mechanism of susceptibility. Methods: A systematic search was conducted of scientific literature databases and conference proceedings up to December 2015 for studies comparing adequately defined HEU (in whom HIV-infection had been excluded through age-appropriate testing) and HU infants for all-cause mortality, all-cause hospitalization or an infection-related morbidity. The systematic review was complemented by a narrative review of additional studies detailing the pattern of infectious morbidity experienced by HEU children without comparison to HU children or without conclusive exclusion of HIV-infection in HIV-exposed infants. Results: Only three of 22 eligible identified studies were designed to primarily compare HEU and HU infants for infectious morbidity. Fourteen were conducted prior to 2009 in the context of limited antiretroviral interventions. Three patterns emerge: 1) causes of morbidity and mortality in HEU infants are consistent with the common causes of childhood morbidity and mortality (pneumonia, diarrheal disease and bacterial sepsis) but occur with greater severity in HEU infants resulting in higher mortality, more frequent hospitalization and more severe manifestations of disease; 2) the greatest relative difference between HEU and HU infants in morbidity and mortality occurs beyond the neonatal period, during mid-infancy, having waned by the second year of life; 3) HEU infants are at greater risk than HU infants for invasive streptococcal infections specifically Group B Streptococcus and Streptococcus pneumonia. Conclusion: To definitively understand HEU infant infectious morbidity risk, substantially larger prospective studies with appropriate HU infant comparison groups are necessary. HEU children would benefit from collaboration amongst researchers to achieve the quality of evidence required to improve HEU infant outcomes globally. HEU infant health and wellbeing, beyond avoiding HIV-infection, deserves a more prominent position in the local and international HIV research agendas.